Estimating Glomerular Filtration Rate in Kidney Transplantation: A Systematic Review of the Diagnostic Accuracy of Creatinine and Cystatin C-Based Equations - Wahyu Agus Prastyo; Artha Investari Nugraheni; Mutia Ruliana Ayuningrum (International Medical Journal Corp. Ltd, 2025)
Introduction: Accurate assessment of glomerular filtration rate (GFR) is paramount for monitoring allograft function and predicting outcomes in kidney transplant recipients (KTRs). Estimated GFR (eGFR) equations, based on endogenous biomarkers like serum creatinine (SCr) and cystatin C (CysC), are universally used, but their performance in the unique KTR population is variable. This systematic review synthesizes the evidence on the diagnostic accuracy of various eGFR equations in adult KTRs. Methods: A systematic search of PubMed, Scopus, and the Cochrane Library was conducted to identify diagnostic accuracy studies comparing eGFR equations to a measured GFR (mGFR) reference standard (e.g., inulin, iohexol, iothalamate, or radioisotope clearance) in adult KTRs. Data on study design, population characteristics, and performance metrics—including bias, precision, and accuracy (proportion of estimates within 30% of mGFR, P30)—were extracted. The methodological quality of included studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool. Results: Seventeen primary research studies involving over 20,000 KTRs were included. The evidence demonstrates that eGFR equations combining both SCr and CysC consistently outperform single-marker equations. The combined Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine-cystatin C equation achieved a P30 accuracy of 86.5% in a large cohort, superior to its creatinine-only (80.4%) and cystatin C-only (77.1%) counterparts. The recently developed, race-free, KTR-specific (KRS) equation showed high accuracy (P30 ranging from 73.0% to 91.3%) and outperformed the general population race-free CKD-EPI 2021 equation. Validation studies of the 2021 race-free CKD-EPI equations found their performance to be comparable to the previous 2009/2012 race-inclusive versions in KTRs, supporting their adoption in this population. Equations developed for specific subpopulations, such as the Berlin Initiative Study 1 (BIS-1) for the elderly, also demonstrated strong performance in older KTRs. Discussion: The superior accuracy of combined-marker equations is attributable to the mitigation of distinct non-GFR determinants associated with each biomarker. The development of the KRS equation marks a significant advancement, highlighting the benefit of population-specific formulas. The comparable performance of race-free equations alleviates concerns about compromising accuracy while promoting health equity. Conclusion: For the most accurate GFR estimation in KTRs, combined SCr-CysC equations are recommended. When only SCr is available, the KTR-specific KRS equation is the preferred choice over general population formulas. The transition to race-free equations is safe and appropriate in the kidney transplant setting.